First Molecular Identification of Cotylophoron cotylophorum in Ecuador and Its Phylogenetic Relationship with Fasciola hepatica - Geanella Barragán-López; Fausto Bedoya-Páez; María Lugo-Almarza; Carolina Fonseca-Restrepo; Francisco Angulo-Cubillán; Edison J. Romero; Jacobus H. de Waard; Armando Reyna-Bello (Pathogens)
Trematode infections caused by Fasciolidae and Paramphistomidae remain widespread in livestock, resulting in substantial economic losses. The two distinct fluke families are difficult to distinguish morphologically, and molecular identification provides the most reliable means of accurate diagnosis. In Ecuador, however, molecular data on these parasites are scarce. In this study, we collected trematodes from cattle rumen and bile ducts, molecularly identified them, and assessed their phylogenetic relationship to Fasciola hepatica to determine their introduction pathways into South America. Genomic DNA was extracted, and PCR was used to amplify the ITS2 (~500 bp) and COXI (~266 bp) regions; all amplicons were Sanger-sequenced. Phylogenetic trees for both markers were constructed using a Maximum Likelihood approach with 1000 bootstrap replicates in CIPRES v3.3. The rumen fluke exhibited 99% ITS2 and COXI similarity to an Indian Cotylophoron cotylophorum strain, while the bile-duct fluke showed 99% ITS2 and 100% COXI similarity to F. hepatica isolates from Australia and Nigeria, respectively. Distinct single-nucleotide polymorphisms (SNPs) in the ITS2 chromatograms suggest a diploid genome structure in both trematode species. This is the first report of C. cotylophorum in Ecuador, and its presence may be linked to the late 19th-century introduction of Zebu cattle (Bos taurus indicus) from India.